ENTERNASIONAL THE SOCIAL COLLABORATION THROUGH INTERACTIVE OUTING CLASS IN MODERN ISLAMIC BOARDING SCHOOL SAIFULLAH AN NAHDLIYAH - Rahayu, Sri (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This community service documents and analyzes a community service experience that aims to improve social collaboration through interactive outing class activities for students of Islamic Boarding School Modern Saifullah An Nahdliyah in Batu Gemuk Village, Deli Serdang Regency, North Sumatra. This service explores the impact of social interaction-based out-of- class activities on Boarding School students in the context of developing social skills, increasing cultural understanding, and developing social cooperation. Through a participatory approach, this service involved students, Boarding School teachers, and village communities in planning, implementing, and evaluating interactive outing classes. The results showed that this activity not only provided a valuable educational experience, but also enriched students' social interaction with the surrounding community. The collaboration between the Boarding School, students, and the community in designing and implementing the interactive outing class has created a supportive environment for knowledge exchange, appreciation of cultural diversity, and improved communication and social cooperation skills. In addition, this activity facilitated the establishment of strong social networks between Boarding School students and the local community. Students not only gain a deeper understanding of the social realities around them, but also learn to become responsible agents of change in moving the community forward. This work underscores the importance of interactive outing classes as an inclusive education model that allows Boarding School students to interact positively with local communities, strengthen social values, and form sustainable collaborations. The practical implication is the need to support and expand similar programs in other Boarding School, as well as build sustainable partnerships with local communities. It is hoped that this service can provide direction for other community service approaches in enhancing social collaboration and strengthening relationships between Boarding School and communities in Indonesia.